Market Orientation and Agile Aesthetic Innovation as Drivers of Business Performance: The Dynamic Adaptive Capability in Indonesia’s Batik Industry - Novie, Muhafidhah; Rachmat, Muhammad; Abu Jalil, Eva Aqilah; Zubaidah, Tantri Risda (Jurnal Aplikasi Manajemen, 2025)
The Indonesian batik industry faces increasing pressure from rapid fashion cycles, digital market transformation, and intensified competition, requiring MSMEs to strengthen market responsiveness while preserving cultural identity. This study examines the effects of Market Orientation, Agile Aesthetic Innovation, and Dynamic Adaptive Capability on Business Performance and tests whether Dynamic Adaptive Capability mediates the relationships between strategic capabilities and performance. A quantitative explanatory design was applied to 220 owners and managers of batik MSMEs in Pekalongan, Solo, Lasem, Madura, and Sidoarjo. Data were collected using a structured questionnaire and analyzed with Partial Least Squares Structural Equation Modeling using SmartPLS 3. The findings show that Agile Aesthetic Innovation is the strongest direct driver of Business Performance, followed by Market Orientation and Dynamic Adaptive Capability. Agile Aesthetic Innovation also positively influences Dynamic Adaptive Capability, whereas Market Orientation does not significantly affect it. The mediation test indicates that Dynamic Adaptive Capability does not significantly mediate the relationships between Market Orientation, Agile Aesthetic Innovation, and Business Performance. These findings suggest that batik MSMEs improve performance mainly through direct market-oriented decisions, rapid aesthetic renewal, and adaptive capability. This study contributes by introducing Agile Aesthetic Innovation as a context-specific capability for culture-based creative MSMEs.